2016
DOI: 10.1016/j.jallcom.2016.07.223
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of symmetrical SrFe0.75Mo0.25O3−δ electrodes in direct carbon solid oxide fuel cells

Abstract: Symmetrical solid oxide fuel cells (SOFCs) that feature nanostructured SrFe 0.75 Mo 0.25 O 3-δ (SFMO) electrodes which are impregnated into porous La 0.9 Sr 0.1 Ga 0.8 Mg 0.2 O 3-δ (LSGM) skeletons by solution infiltration technique are prepared. The symmetrical SOFCs are investigated in detail by operating with 5 wt.% * Corresponding author. Tel. /fax: +86 20 22236168. © 2016. This manuscript version is made available under the Elsevier user license http://www.elsevier.com/open-access/userlicense/1.0/ 2 Fe-lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(10 citation statements)
references
References 26 publications
(49 reference statements)
0
10
0
Order By: Relevance
“…Generally, Fe‐based materials are regarded as the high‐efficiency and stable catalysts for catalyzing the Boudouard reaction, and the Fe‐loaded activated carbon has been proven to be one of the best carbon fuels for DC‐SOFCs . To develop higher activity catalysts for Boudouard reaction and thus improve the cell performance, carbon fuels containing 3, 5, 7, and 10 wt% Ba and pure activated carbon were prepared and evaluated in DC‐SOFCs at 850 °C with 5 wt% Fe‐loaded activated carbon as a benchmark.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, Fe‐based materials are regarded as the high‐efficiency and stable catalysts for catalyzing the Boudouard reaction, and the Fe‐loaded activated carbon has been proven to be one of the best carbon fuels for DC‐SOFCs . To develop higher activity catalysts for Boudouard reaction and thus improve the cell performance, carbon fuels containing 3, 5, 7, and 10 wt% Ba and pure activated carbon were prepared and evaluated in DC‐SOFCs at 850 °C with 5 wt% Fe‐loaded activated carbon as a benchmark.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, the solid‐state electrolyte is more suitable for practical application in comparison with the liquid electrolyte in a DCFC due to safety issues. For these reasons, the direct carbon solid oxide fuel cell (DC‐SOFC) with a ceramic oxygen ion conductor as the electrolyte has attracted a particular interest because it is an all‐solid‐state fuel cell directly operating with solid carbon as fuel without any liquid medium or purging gas . In fact, it also can be regarded as a SOFC operated with carbon fuel.…”
Section: Introductionmentioning
confidence: 99%
“…VIII metals greatly acceleratev the reaction rate of reverse Boudouard reaction [4,5] . Perovskite is an extensively studied material in DC-SOFC anode, which is mixed ionic and electronic conduction(MIEC) [6][7][8][9] . Rencently, A-site ordered layered double perovskite materials have received more and more attention in the field of fuel cells, such as PrBa 0.5 Sr 0.5 Co 2-…”
Section: Introductionmentioning
confidence: 99%
“…Based on this mechanism, the performance of DC-SOFC will be affected by the electrochemical oxidation of CO at TPBs in anodes, the Boudouard gasification and mass transport between anode and solid carbon fuel [25][26][27]. Besides development of new anode material and microstructure [19,[28][29][30], which can improve catalytical activity, mass transport, ionic or electronic conductivities of anode, plenty of experimental evidence demonstrates that carbon activity and transport properties in the anode can significantly influence the DC-SOFC performance [3,13,17,21,25,[31][32][33][34]. Liu et al [31] operated a tubular SOFC fed with the activated carbon and the results indicated that the fuel gas in the anode was insufficient and the mass transport in the anode was poor.…”
Section: Introductionmentioning
confidence: 99%